Application of oxygen enrichment and adiabatic humidification to suction air for reducing exhaust emissions in a gasoline engine. Issue 1 (31st December 2023) - Kapusuz, Murat; Çakmak, Abdülvahap; Özcan, Hakan
ABSTRACT: This paper aims to reduce the exhaust emissions of a gasoline engine by conditioning the engine intake air. The oxygen enrichment of inlet air to reduce the HC and CO emissions and humidifying the inlet air to control NOX emissions was applied. The intake air oxygen concentration was increased from 21% to 25% by 2% interval. The oxygen enrichment of the engine inlet air increased the combustion rate, and thus combustion improved, and thermal efficiency increased. This situation led to a reduction in HC emissions and CO emissions. However, the combustion improvement caused a striking rise in NOX emissions because of the high cylinder temperature and high oxygen concentration. This undesirable effect was tried to be alleviated by adiabatic humidification of the engine inlet air. For this purpose, the relative humidity of the intake air was increased from 35% to 65% before and then to 85%. For this, the intake air passed through the conditioning chamber, the dry thermometer temperature lowered by 4 °C for a relative humidity of 85% thanks to the evaporative cooling of water. The results showed that oxygen enrichment caused a 13.5% and 9.3% increase in thermal efficiency in order of half and full load. The humidification method resulted in a 14.3% and 18.3% decrease in thermal efficiency for half and full load. The results also showed that the humidification method could only control NOX increment generated at half load and 23% oxygen condition.